New Dissimilarity Measures On Picture Fuzzy Sets And Applications / Le Thi Nhung, Nguyen Van Dinh, Ngoc Minh Chau, Nguyen Xuan Thao - Le, Thi Nhung
The dissimilarity measure between fuzzy sets/ intuitionistic fuzzy sets/picture fuzzy sets are studied and applied in various matters. In this paper. we propose some new dissimilarity measures on picture fuzzy sets. These new dissimilarity measures overcome the restrictions of all existing dissimilarity measures on picture fuzzy sets. After that, we apply these new measures to the pattern recognition problem . Finally we introduce a multi - criteria decision making (MCDM) method that use the new dissimilarity measures and apply them in the supplier selection problems